Epstein–Barr Virus+ Smooth Muscle Tumors as Manifestation of Primary Immunodeficiency Disorders - Magg, Thomas; Schober, Tilmann; Walz, Christoph; Ley-Zaporozhan, Julia; Facchetti, Fabio; Klein, Christoph; Hauck, Fabian (Frontiers in Immunology, 2018)
EBV positive smooth muscle tumors constitute a very rare oncological entity. They usually develop in the context of secondary immunodeficiency caused by human immunodeficiency virus infection or immunosuppressive treatment after solid organ transplantation. However, in a small fraction of predominantly pediatric patients, EBV positive smooth muscle tumors may occur in patients with primary immunodeficiency disorders such as GATA2 and CARMIL2 deficiency. In secondary immunodeficiencies and when the underlying condition can not be cured, the treatment of EBV positive smooth muscle tumors is based on surgery in combination with antiretroviral and reduced or altered immunosuppressive pharmacotherapy, respectively. Importantly, without definitive reconstitution of cellular immunity, long term survival is poor. This is particularly relevant for patients with EBV smooth muscle tumors on the basis of primary immunodeficiency disorders. Recently allogeneic hematopoietic blood stem cell transplantation resulted in cure of immunodeficiency and EBV positive smooth muscle tumors in a GATA-2 deficient patient. We propose that in the absence of secondary immunodeficiency disorders patients presenting with EBV positive smooth muscle tumors should be thoroughly evaluated for primary immunodeficiency disorders. Allogeneic hematopoietic stem cell transplantation should be taken into consideration, ideally in the setting of a prospective clinical trial.